The Influence of Service Quality and Store Atmosphere on Customer Satisfaction - Alfreldo, Farhan; Wahyuningtyas, Yunita Fitri (Research Horizon, 2026)
The increasingly intense competition in the café industry requires business owners to create sustainable customer satisfaction to maintain competitiveness. Customer satisfaction is influenced by various factors, particularly service quality and store atmosphere that are directly experienced by customers. This study aims to examine the effect of service quality and store atmosphere on customer satisfaction. A quantitative approach was applied using a survey method, with questionnaires distributed to 130 respondents. Data were analyzed using SPSS version 27, including validity and reliability tests as well as multiple linear regression analysis. The results show that service quality has a positive and significant effect on customer satisfaction. Likewise, store atmosphere also has a positive and significant effect on customer satisfaction. Simultaneously, service quality and store atmosphere jointly have a significant positive effect on customer satisfaction. These findings indicate that improving service quality and creating a comfortable and attractive store atmosphere are essential to enhancing customer satisfaction and strengthening the competitiveness. This study contributes to marketing management theory by examining the influence of service quality and store atmosphere on customer satisfaction and provides a practical basis for improving service quality, store atmosphere, and marketing strategies to enhance customer satisfaction.